Burrowing Into the Past: Extending Niche Space Models of Procellariiform Breeding Grounds by Merging Fossil and Historic Data - Bellvé, André M.; Wilmshurst, Janet M.; Wood, Jamie R.; Whitehead, Edin; Scofield, R. Paul; Worthy, Trevor H.; Gaskin, Chris P.; Perry, George L. W. (Diversity & distributions, 2025)
ABSTRACT Aim Predicting species' potential distributions and niches requires multi‐scale data encompassing the past and present. Increasingly, researchers have advocated using historical context to inform ecological niche models (ENMs). Two key sources of past distributions are fossils and historical records. Fossils are subject to sampling and taphonomy biases but offer insights into temporal dynamics over millennia. Historical records are filtered by human perceptions over a shorter temporal window, but compared to fossils, provide different contextual information from a potentially broader range of habitats. New Zealand (NZ) has a relatively short history of human occupation, with rich fossil and historical literature archives. Approximately 25% of the world's seabirds breed in NZ, nearly half of which are burrowing procellariiforms. Since human arrival in NZ, most procellariiforms have declined in abundance and breeding ranges, primarily due to introduced mammalian predators. We combined record sources to improve ENMs of burrowing procellariiform breeding colonies and reconstruct narratives of decline. Location Aotearoa New Zealand. Methods We fitted ENMs using a maximum entropy algorithm and mixed‐principal component analysis for four sets of occurrence records (fossil, historic, historic + fossil and post‐1990) of burrowing procellariiform breeding colonies, where taxa were grouped by functional traits. Results For all procellariiform trait groups, the breeding niche space captured separately by the fossils and historical data had low overlap, reflecting different environmental conditions. The combined fossil + historic datasets predicted a niche that overlapped the post‐1990 observed niche. Moreover, the fossil and historic datasets combined demonstrated that breeding grounds, now restricted mainly to predator‐free settings, were once more widespread and extended further inland throughout NZ. Main Conclusions Historic and fossil occurrence records can complement each other by mitigating biases unique to either dataset to better resolve these procellariiform trait groups ecological breeding niches. Together, such records provide critical insights into the past drivers of species range contractions, contextualising current ecosystems and informing species management planning.